1991
DOI: 10.1002/j.1460-2075.1991.tb04956.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular base pairing between the nematode spliced leader and its 5′ splice site is not essential for trans-splicing in vitro.

Abstract: The spliced leader RNAs of both trypanosomes and nematodes can form similar secondary structures where the trans‐splice donor site is involved in intramolecular base pairing with the spliced leader sequence. It has been proposed that this base pairing could serve to activate autonomously the SL RNA splice donor site. Here, we have examined exon requirements for trans‐splicing in a nematode cell free system. Complete disruption of secondary structure interactions at and around the trans‐splice donor site did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
1
23
1
Order By: Relevance
“…Although this level of dissimilarity has not been shown in other species containing multiple spliced leaders, this finding is not necessarily unexpected. Mutagenesis studies have shown there is considerable flexibility in the sequence and structural requirements for splicing of the C. elegans SL-1 RNA (34,35). We now have multiple examples of genes whose mRNAs can accept either SL-A or -B.…”
Section: Discussionmentioning
confidence: 99%
“…Although this level of dissimilarity has not been shown in other species containing multiple spliced leaders, this finding is not necessarily unexpected. Mutagenesis studies have shown there is considerable flexibility in the sequence and structural requirements for splicing of the C. elegans SL-1 RNA (34,35). We now have multiple examples of genes whose mRNAs can accept either SL-A or -B.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was hypothesized that the base pairing of the trans-splice site with the SL mimicked the interaction of the 5Ј splice site with the U1 snRNA (5). However, the Ascaris SL RNA can function in vitro without such base pairing (34). Indeed, the entire SL exon is dispensable and can be replaced with sequences varying in length from two to 246 nt while maintaining the ability to trans splice (34).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, different groups have reported very different results when they mutate or delete portions of the SL itself (15,19,32,34,47,56). In nematodes it is clear that the SL1 sequence can be replaced by unrelated sequences of various lengths without loss of in vitro trans splicing (34), but at least one SL mutation was found to prevent trans splicing in vivo (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, conservation of the spliced leader sequence, length, or structure is not required for trans-splicing in vitro (46). Similarly, it is possible that the SL2 sequence itself may not be required for the trans-splicing reaction, but for the transcription of the SL2 RNA gene.…”
Section: Discussionmentioning
confidence: 99%